2023
DOI: 10.21037/atm-23-1384
|View full text |Cite
|
Sign up to set email alerts
|

Management of complications following implant-based breast reconstruction: a narrative review

Dean H. Meshkin,
Joseph M. Firriolo,
Nolan S. Karp
et al.

Abstract: Background and Objective Complications associated with implant-based reconstruction have a spectrum of severity with sequelae ranging from mild aesthetic deformities to additional surgery, reconstructive failure and systemic illness. The purpose of this narrative review of the literature is to provide updated evidence-based information on the management of complications in implant-based reconstruction. Methods A systematic search of PubMed, OVID MEDLINE and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…The risk of presenting complications in breast surgery is ~12% in general population, the most frequent within this group being hematoma, infection, dehiscence, and seroma [ 6 ]. In breast surgery, it is reported that hematoma formation occurs in ~5.1% of the operated patients of which 1.1% will require blood transfusion [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of presenting complications in breast surgery is ~12% in general population, the most frequent within this group being hematoma, infection, dehiscence, and seroma [ 6 ]. In breast surgery, it is reported that hematoma formation occurs in ~5.1% of the operated patients of which 1.1% will require blood transfusion [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature also contains data on other morphological variants of the reaction of breast tissue to the implant [11,31,34]. The most common among them is synovial metaplasia (transdifferentiation) [7,27], in which epithelioid cells similar to synovial cells appear on the inner surface of the fibrous capsule bordering the implant, and in general, this structure resembles a joint [28].…”
Section: Introductionmentioning
confidence: 99%